Prevalence of chlamydia trachomatis in patients subjected to assisted reproduction techniques. Cienfuegos, 2016-2018 - Práxedes Rojas Quintana; Dainalith Dulciree Guedez Villalobos; Aimé María Reyes Pérez; Neisy Chávez González; Elodia Rivas Alpízar (Medisur, 2023)
Background: Chlamydia trachomatis is the causal agent of one of the most common sexually transmitted infections in the world. Causes cervicitis, endometritis and salpingitis; after effects include pelvic inflammatory disease, ectopic pregnancy, and infertility due to tubal obstruction. Objective: to determine the prevalence of Chlamydia trachomatis infection in patients undergoing assisted reproductive techniques. Methods: case series study developed at the Dr. Gustavo Aldereguía Lima Hospital General Universitario, Cienfuegos, during 2016-2018. It included patients subjected to assisted reproduction techniques who were infested with Chlamydia trachomatis. The variables age, personal and gynecological pathological history, number of sexual partners, years of infertility, history of intrauterine device use, history of pelvic inflammatory disease, Chlamydia test result, as well as criteria or not for in vitro fertilization were analyzed as an indicator that damage occurred at the level of the tubes. Results: the age was between 19 and 40 years old, with an average of 35.7 years. The germ was detected in 42% of the couples, with a predominance of those from Cienfuegos. 47.6% of the patients who had chlamydiasis reported having had from one to three partners. 54%, due to their involvement, required in vitro fertilization. There was a high incidence over time being infertile, with 72.6% over four years. Conclusions: Chlamydia trachomatis infections can influence fertility in women.